2021
DOI: 10.3389/fphar.2021.565724
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Remodeling in Human Heart Failure after Cardiac Resynchronization Therapy Is Associated With Reduced RHO-Kinase Activation

Abstract: Background: Reverse remodeling is a clinically relevant endpoint in heart failure with reduced ejection fraction (HFrEF). Rho-kinase (ROCK) signaling cascade activation correlates with cardiac remodeling and left ventricular (LV) systolic dysfunction in HFrEF patients. Cardiac resynchronization therapy (CRT) is effective in HFrEF, especially when there is a left bundle block, as this treatment may stimulate reverse remodeling, thereby improving quality of life and prolonging survival for patients with this sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Higher levels of ROCK activity have also been reported in patients with metabolic syndrome (MS) [161,162]. In HFrEF patients, a significant reduction in left atrial diameter was observed three months after effective resynchronization therapy, which was associated with a significant reduction of ROCK activation in circulating leukocytes [163]. Although GLP-1 RA treatment reduced ROCK activation and hypertrophy in cultured cardiac myoblasts stimulated by angiotensin II [155], there are no available human data on the effect of GLP-1 RA on ROCK activation in patients with MS or T2D, and GLP-1 RA may reduce ROCK activation in PBMCs, as well as body weight, plasma glucose, and insulin levels; increase aerobic capacity; and possibly decrease left atrial volume while improving left atrial function, potentially preventing HF in patients with MS or T2D.…”
Section: Effects Of Glp-1r Agonism On the Ras Cardiac Remodeling Path...mentioning
confidence: 95%
“…Higher levels of ROCK activity have also been reported in patients with metabolic syndrome (MS) [161,162]. In HFrEF patients, a significant reduction in left atrial diameter was observed three months after effective resynchronization therapy, which was associated with a significant reduction of ROCK activation in circulating leukocytes [163]. Although GLP-1 RA treatment reduced ROCK activation and hypertrophy in cultured cardiac myoblasts stimulated by angiotensin II [155], there are no available human data on the effect of GLP-1 RA on ROCK activation in patients with MS or T2D, and GLP-1 RA may reduce ROCK activation in PBMCs, as well as body weight, plasma glucose, and insulin levels; increase aerobic capacity; and possibly decrease left atrial volume while improving left atrial function, potentially preventing HF in patients with MS or T2D.…”
Section: Effects Of Glp-1r Agonism On the Ras Cardiac Remodeling Path...mentioning
confidence: 95%